Boron Carbide as an Electrode Material: Tailoring Particle Morphology to Control Capacitive Behaviour - Avcioglu, Suna; Buldu-Akturk, Merve; Erdem, Emre; Kaya, Figen; Kaya, Cengiz (MDPI, 2023)
In this study, boron carbide powders consisting mainly of nano/micro fibers or polyhedral-equiaxed particles were synthesized via the sol-gel technique, and the influence of particle morphology on electrochemical performance of boron carbide electrodes was investigated. Thermal decomposition duration of the precursors played a determinant role in the final morphology of the synthesized boron carbide powders. The morphology of boron carbide powders successfully tuned from polyhedral-equiaxed (with similar to 3 mu m average particle size) to nano/micro fibers by adjusting the thermal decomposition duration of precursors. The length and thickness of fibers were in the range of 30 to 200 mu m and sub-micron to 5 mu m, respectively. The electrochemical performance analysis of boron carbide powders has shown that the particle morphology has a considerable impact on the boron carbide electrodes electrochemical performance. It was found that the synergetic effects of polyhedral-equiaxed and nano/micro fiber morphologies exhibited the best electrochemical performance in supercapacitor devices, resulting in the power and energy density of 34.9 W/kg and 0.016 Wh/kg, respectively.
Keywords: boron carbide (B4C); morphology; supercapacitor; electrode; energy storage; ELECTROCHEMICAL PROPERTIES; CARBON; ENERGY; NANO; SPECTROSCOPY; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering; Physics